Strategies for sustainable improvement of the wheat phenotype - Giordano, Nicolas (My University, 2025)
This dissertation explores strategies for wheat yield and quality improvement in regional (United States Great Plains) and global scales. Throughout six individual chapters, I collaborate with experts from diverse backgrounds to explore multiple layers of biological organization -from genetic to social networks- aiming to understand drivers of wheat grain yield and quality. In the first chapter we used quantitative literature synthesis methods to (i) assess the effect of N applications to wheat after flag leaf visible (GS 37) on grain yield and grain protein concentration; and to assess the variation in these responses with (ii) N fertiliser management, (iii) environmental factors, and (iv) physiological traits. Overall, late-season N fertilisation was neutral for grain yield and increased grain protein concentration with a pooled estimate of 3.96%. The second chapter explored relations of wheat yield and grain protein concentration in response to N input and its physiological basis from the perspective of phenotypic plasticity. Grain yield plasticity was positively associated to yield in high-yielding environments without N limitations with no cost in low yielding environments, and associated to harvest index. Grain protein plasticity was a positively associated to protein in high protein environments without N limitations. In the third chapter we proposed a Bayesian hierarchical framework to model the variance of grain yield response to plant density. We identify the plant density in each seed size, seed treatment and environment combination that maximizes the expected yield and minimizes yield variance. In the fourth chapter we used data from variety trials conducted between 2000 and 2022 and cultivars released between 1967 and 2022, to explore time trends in phenotypic plasticity and heritability of yield. Breeding for yield and agronomic adaptation increased phenotypic plasticity of yield at 0.5% year -1; broad sense heritability of yield decreased from 0.23 in 1993 to 0.15 in 2017. Genome-wide-association analysis shows genomic regions associated with yield varied between high yielding and stressful environments and were partially independent of those associated with yield plasticity. Newer cultivars have a higher frequency of alleles associated with yield and its plasticity. The fifth chapter aims to narrow winter wheat yield gaps in the US Great Plains, by understanding trade-offs and synergies between stripe rust resistance and yield phenotypic plasticity under varying management and environment. High yield stability and susceptibility to stripe rust comes at the expense of yield gaps regardless of environment yield potential and conditions conducive to stripe rust development. In the last chapter, we propose a three-step process to advance food systems sustainability, using wheat as a case study. This process is informed by data collected during a two-day expert elicitation workshop involving 46 stakeholders from the wheat industry. First, we move toward an operational definition of sustainability grounded on wheat value chain stakeholders. Second, we propose a framework a framework to identify common and diverging priorities across sectors of the value chain. Third, we advance on collaboration strategies to advance on a unified sustainability stamp on a loaf of bread, that agrees with the conceptual definition of sustainability. We showed that (i) there is a priori consensus across the wheat industry on a definition of sustainability and, (ii) the ranking of sustainability priorities, was not associated to the level of agreement of a given sustainability indicator across the wheat industry, revealing each sector has its own unique sustainability goals.
Keywords: Bayesian statistics; Crop ecology; Sustainability; Nitrogen; Stripe rust; Yield gap